Plataformas microfluídicas descartáveis: desenvolvimento, caracterização e aplicações em química bioanalítica - Chagas, Cyro Lucas Silva (2018)
The development of miniaturized devices promoted a real revolution in modern analytical chemistry. In addition, the improvement of microfabrication technologies has made it possible to create ever smaller and more robust devices. However, most of these devices still demand sophisticated and expensive instrumentation in their manufacturing process, often requiring controlled environments or clean rooms. In view of the need to produce these miniaturized devices in a more accessible way, the present thesis presents the manufacture of alternative, disposable and low cost microfluidic platforms and devices for bioanalytical applications. The methodologies covered in this thesis include: the manufacture of low cost pencil-drawn graphite electrodes on office paper, used in the quantification of inorganic cations (K+ and Na+) in human tears; the manufacture of electrophoresis chips with thermolaminated paper channels with attached graphite electrodes for the monitoring of the electrophoretic separation of biomolecules (albumin and creatinine); and finally, it presents the use of a 3D microfluidic device for the generation of droplets into the microchannel and the manufacturing process of a thermolaminated polyester dispositive for flow injection analysis, both for the analysis of drugs (ascorbic acid and midazolam maleate) in medicines. All analyzes used the same method of capacitively coupled contactless conductivity detection. The proposed graphite electrodes presented excellent analytical performance with good reproducibility. The detection limits found for K+, Na+ and Li+ were 4.9, 6.8 and 9.0 μM, respectively. In addition, the concentration found for K+ and Na+ in the tear samples were, respectively, 20.8 and 101.2 mM for sample A and 20.4 and 111.4 mM for sample B. Experiments using the proposed paper-based microchip have successfully demonstrated the separation of bovine serum albumin and creatinine within 150 s with baseline resolution. The detection limits for albumin and creatinine were 20 and 35 mM, respectively. The quantification of ascorbic acid in a vitamin supplement, through the generation of droplets in the 3D device, was successfully demonstrated with a linear range of 3 to 24 mg/mL and a detection limit of 1.1 mg/mL. The quantification of midazolam maleate in tablets, using a flow injection in the polyester device showed a linear behavior between 0.5 and 4.0 mg/mL and a detection limit of 17 µg/mL. The devices proposed in this thesis allowed the realization of low cost assays with reduced analysis time. In addition, the manufacturing processes demonstrated simplicity and quickness, without the need for sophisticated instrumentation, allowing the use of these devices for applications in clinical analysis and quality control.